International education: politics and policies - GARCÍA RUIZ, Mª José (Colección de libros electrónicos en Xebook, 2013)
The present book aims to analyse key features of the field of International Education. It also intends to study crucial elements of the relevant dimensions of the dichotomy Politics versus Policies. Educational policy and politic together constitute a vast field of research and intellectual endeavour. 'Policy' and 'Politics' are two words that are often confused with regard to their connotations. There is in fact some difference between the two words. 'Policy' is a 'principle'. 'Politics' is all about organizational process.